2023
DOI: 10.1002/ajpa.24720
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal household size and composition are associated with infant fecal bacterial diversity in Cebu, Philippines

Abstract: Objectives The gut microbiome (GM) connects physical and social environments to infant health. Since the infant GM affects immune system development, there is interest in understanding how infants acquire microbes from mothers and other household members. Materials and Methods As a part of the Cebu Longitudinal Health and Nutrition Survey (CLHNS), we paired fecal samples (proxy for the GM) collected from infants living in Metro Cebu, Philippines at 2 weeks (N = 39) and 6 months (N = 36) with maternal interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…In a large, multi‐country study, Lane et al (2019) did not detect associations between household composition and gastrointestinal microbiome diversity, although household size and the presence of extended family were nonlinearly associated with the differential abundance of specific taxa, including Enterobacter and Lactobacillus . Manus et al (2023) reported that prenatal household size predicted Shannon (alpha) diversity in infancy, although the association was negative at 2 weeks of age and positive at 6 months of age. However, Thompson et al (2015) found that infants, aged 2–14 months, enrolled in out‐of‐home daycare had higher diversity and species richness compared to infants cared for at home, as well as significantly greater Lactobacillus and Sutterella .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large, multi‐country study, Lane et al (2019) did not detect associations between household composition and gastrointestinal microbiome diversity, although household size and the presence of extended family were nonlinearly associated with the differential abundance of specific taxa, including Enterobacter and Lactobacillus . Manus et al (2023) reported that prenatal household size predicted Shannon (alpha) diversity in infancy, although the association was negative at 2 weeks of age and positive at 6 months of age. However, Thompson et al (2015) found that infants, aged 2–14 months, enrolled in out‐of‐home daycare had higher diversity and species richness compared to infants cared for at home, as well as significantly greater Lactobacillus and Sutterella .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lane et al (2019) sequenced the V1‐V3 region of the 16S rRNA gene, used unrarefied data to generate alpha diversity, used Observed Richness instead of Chao1, and conducted differential abundance tests with the Analysis of Compositions of Microbiomes (ANCOM) rather than DESeq2. Manus et al (2023) sequenced the V4‐V5 region and also used ANCOM. Thompson et al (2015) sequenced the V1‐V2 region of the 16 s rRNA gene and used rarefied data but also used Observed Richness.…”
Section: Discussionmentioning
confidence: 99%